Epidemiological profile of burned patients at the Clinical Hospital of the Federal University of Uberlândia in Brazil - Douglas Ravel Neto Diniz Ribeiro; Sinval Soares Cruvinel; Phelipe Augusto Costa; Hiléia Carolina de Oliveira Valente; Tauã Richel Belchior da Costa (Revista Brasileira de Cirurgia Plástica)
Introduction: Burns are lesions caused by agents external to organic tissues, in which there is the destruction of the epithelial lining and/or mucous membranes in varying depth and extension. This study aims to analyze the epidemiological profile of burned patients admitted to the Clinical Hospital of the Federal University of Uberlândia, Minas Gerais, Brazil. Methods: Data were obtained by collecting medical records of patients admitted to the emergency room and burn Unit of the Hospital de Clínicas, from January 1, 2015, to December 31, 2019. Results: Of the 305 patients analyzed, 59.2% were male, the age group from 0 to 9 years was the most representative (24.03%) and brown ethnicity with the highest number of episodes (42.53%). Regarding hospitalization length, 57% of the cases were hospitalized less than ten days and the mean total hospitalization time was 26.61 days. It was found that the most frequent incident was exposure to explosive agents or combustion of flammable substances (43.51%) and that liquid alcohol was the most common etiological agent (30.51%). Conclusion: The relevance of the epidemiological profile is observed since it identifies the main risk groups. According to the references used, the importance of prevention and surveillance is highlighted, focusing on reducing morbidity and mortality.